Narratives from a wetland: sustainable management in Lukanga, Zambia - Mapedza, Everisto D.; Geheb, Kim; van Koppen, Barbara; Chisaka, J. (Informa UK Limited, 2012)
Wetlands are a key livelihood resource in southern Africa. Historically they have been managed using local knowledge systems, but these systems have in many instances been undermined by colonial and postcolonial legal requirements. The IUCN's Ramsar initiative, supported by organisations such as BirdLife International and the WWF, seeks to protect wetland resources. This qualitative study examined the political ecology of the Kapukupuku and Waya areas of the Lukanga wetlands in Zambia, designated a Ramsar site. This designation has given rise to competing 'narratives' by politicians and local community leaders over how Lukanga should be managed and used, and the resulting conflict is threatening its sustainability. The paper warns that the various parties' arguments are value-laden and that power asymmetry threatens to exclude poor local communities. Policy must take power interests into account to ensure that developments in the name of the poor really do benefit the poor.